THE EFFECT OF STEM-PjBL LEARNING MODEL ON CRITICAL THINKING SKILLS ON EFFORTS AND ENERGY TOPIC - Sari, Amalia Intan; Muttaqiin, Arief; Yurnetti; Zahra, Firda Az (SEMESTA: Journal of Science Education and Teaching, 2024)
This study aims to determine the effect of the STEM-PjBL learning model on the critical thinking skills in grade VIII students an topic efforts and energy. This type of research is Quasi Experimental with a Nonequivalent Control Group Design. This research was carried out in VIII grade at SMPN 14 Padang, West Sumatra. The sample taken by purposive sampling techniques so that 32 students of class VIII. 2 as the experimental class and 32 students of class VIII.1 as the control class. The instrument used is a test in the form of essay questions. The results showed that the hypothesis was accepted because the calculation showed sig < 0.05. It can be concluded that overall the use of the STEM-PjBL learning model affects the critical thinking skills students.